Utilization of intravenous antibiotics supplied by in-patient pharmacy, Hospital Tuanku Fauziah to wards - Wan Mahamad, Wan Nor Albaniah (2017)
Antibiotics are widely used - their breakthrough in combatting illnesses is proven effective making them commonly prescribed by physicians for patients; both warded and outpatients. Of that statement, what are the A-list intravenous (IV) antibiotics supplied by inpatient pharmacy (IPD) of Hospital Tuanku Fauziah (HTF) to wards? Which might be the most top of the list prescribed and are there any ward(s) that use more A-list IV antibiotics than the rest? In this project the usage of the IV antibiotics will be observed through data extraction as recorded in bin cards. This observation covers only those supplied by IPD excluding that in satellite pharmacy of HTF. 3-month duration is chosen for data extraction. Since this was a prospective study, we use the latest data obtained from November 2016 to January 2017. Though the data is taken mainly and purely from bin cards alas, there might still be human errors - wrongly recording of data, inaccurate data extraction, not recorded or any changes made by physician such as omitting the treatment. Required data is then typed in the IBM SPSS Statistics 23 and also Microsoft Excel 2010 to be analyzed and visualized to graphs. This study shows that highest of A-list IV antibiotic used was cefuroxime 750mg vials that were used by literally all the wards within IPD in HTF service. Having small sample size, a chi square test is undependable to check whether any significance between usage of IV cefuroxime and wards hence Fisher's exact test is implemented. The result was negative as there is no significance between the usage of lV and wards. On the other hand, IV linezolid lg has the least use which is zero usage in all the 3-month duration as it is mainly used for those with rare complicated infections - deeming as last resort. Kl has the least usage of A-list IV antibiotic and T4 is the most. Having T4 as a medical discipline ward, that consists of patients with various health conditions such as diabetes, hypertension, etc. As T4 is not the only ward of multidiscipline, its usage was the highest and no definitive reason can be achieved from this study. How the usage of A-list IV antibiotic relates to wards was unclear and requires further research.